A new classification for the diagnosis of superficial non‐ampullary duodenal epithelial tumors using endocytoscopy: A prospective study. Issue 11 (28th June 2021) - Muramoto, Takashi; Ohata, Ken; Sakai, Eiji; Inamoto, Rin; Kurebayashi, Marie; Takayanagi, Syunya; Kimoto, Yoshiaki; Suzuki, Yuichiro; Ishii, Rindo; Ono, Kohei; Negishi, Ryoju; Takita, Maiko; et al.
Abstract: Background and Aim: Although the frequency of endoscopic diagnosis of superficial non‐ampullary duodenal epithelial tumors (SNADETs) has been increasing in recent years, no criteria for the endoscopic diagnosis of these tumors have been established yet. The aim of this study was to assess the usefulness of endocytoscopy for diagnosis SNADETs and to establish new criteria. Methods: This prospective study was conducted at the NTT Medical Center Tokyo from May 2019 to July 2020, and a total of 100 consecutive SNADETs were enrolled. All the endocytoscopic images of the lesions and surrounding normal mucosa were classified into three groups according to the degree of structural atypia and the nuclear morphology and size. The endocytoscopic diagnoses using endocytoscopic classification was compared with the final histopathological diagnoses. Results: Data of 93 patients with 98 lesions were included in the analysis. The preoperative diagnosis by endocytoscopy coincided with the final histopathological diagnosis in 85 (86.7%) of 98 SNADETs. In addition, the sensitivity and specificity for VCL 4/5 were 87.7% and 85.4%, respectively. In contrast, the accuracy, sensitivity, and specificity of preoperative diagnosis by biopsy were 64.3%, 50.9%, and 82.9%, respectively. Preoperative diagnosis by endocytoscopy showed significantly superior accuracy and sensitivity as compared with preoperative biopsy diagnosis ( P < 0.001, respectively). Conclusions: This new classification (endocytoscopic classification) allows prediction of the tumor histopathology in real time, during endocytoscopy without biopsy, and is expected to be of help in determining the appropriate therapeutic strategies for individual cases of SNADETs. (Clinical trial registration number: UMIN000038643.)